Overview on Regional Economic Development Gaps across the EU - Mihaela Onofrei; Elena Cigu (CES Working Papers, 2017)
Despite existing policies of regional development and cohesion at the national and the EU level, economic regional inequalities or disparities stay relatively high or decrease too slowly. In this context, policies to reduce economic regional disparities in the European Union are a constant concern both for policy-makers and for theoretical and empirical research because of the strong impact on sustainable development in general. In this study we combine elements of theoretical and policy discussions with the empirical assessment of economic regional development in the European Union in order to identify the state of regional disparities, what factors are favouring unbalanced growth in different regions of the EU and to find an appropriate theoretical setting to understand, explain and reduce with regional inequality in the EU
Keywords: 330; regional economic development; regional disparities; cohesion policy